2013
DOI: 10.1002/ams2.10
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps, damage‐associated molecular patterns, and cell death during sepsis

Abstract: In addition to pathogen-associated molecular patterns from invasive microorganisms, alarmins, which are major components of host defense mechanisms, are involved in the pathophysiology of sepsis. In fact, the magnitude of the insult is defined according to the damage-associated molecular pattern (DAMP), which is composed of alarmins as well as pathogen-associated molecular patterns, such as those involving nucleosomes, histones, and DNA. Regarding the antimicrobial mechanism of neutrophils, an alternative non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…According to a report by Xu and colleagues [ 41 ], histones H3 and H4 have a highly damaging effect on endothelial cells; an intense accumulation of neutrophils is seen in the lungs when histones are injected intravenously into mice, and peri-bronchoalveolar bleeding and thrombus formation is observed, findings that were minimized when an antibody against H4 was administered. We also confirmed the remarkable lung edema, bleeding and thrombus formation in a mouse model after the intravenous administration of histone H3 [ 45 ] (Figure 4 ). Histones are DNA-binding proteins with a positive charge and their toxicity can be diminished by binding of heparins, which are highly sulfated and negatively charged.…”
Section: Neutrophil Extracellular Trap Formationsupporting
confidence: 78%
“…According to a report by Xu and colleagues [ 41 ], histones H3 and H4 have a highly damaging effect on endothelial cells; an intense accumulation of neutrophils is seen in the lungs when histones are injected intravenously into mice, and peri-bronchoalveolar bleeding and thrombus formation is observed, findings that were minimized when an antibody against H4 was administered. We also confirmed the remarkable lung edema, bleeding and thrombus formation in a mouse model after the intravenous administration of histone H3 [ 45 ] (Figure 4 ). Histones are DNA-binding proteins with a positive charge and their toxicity can be diminished by binding of heparins, which are highly sulfated and negatively charged.…”
Section: Neutrophil Extracellular Trap Formationsupporting
confidence: 78%
“…20,21,33 In sterile inflammation, NETs enhance the pro-inflammatory response through the cytotoxicity of free histones, 34 transformation of pro-IL-1β into active IL-1β by NET-based enzymes, 35 and direct action as a DAMP signal for other immune cells. 18,20 NETs also serve as attachment hubs for bactericidal enzymes such as MPO, leukocyte proteases, and LL-37, an enzyme that serves both chemotactic and antimicrobial functions. 36 Interestingly, MPO activity can serve as an additional amplifying component of the inflammatory response; in the lung, genetic knockdown of MPO decreased neutrophil recruitment and subsequent cytokine and chemokine production by other immune cell types.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown a role for neutrophils-namely, NETosisin sterile inflammation, which may be triggered by release of danger-associated molecular patterns (DAMPs). 18 In a murine model of atherosclerosis, NETs were found to prime macrophageal release of pro-inflammatory cytokines via activation of Th-17 cells. 19 Similarly, in the liver, NETosis exacerbated the inflammatory response to experimental ischemia/reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in previous studies, the initiation of NETosis results in the release of damage-associated molecular patterns, which trigger an innate immune and inflammatory cascade (31). TLRs are important sensors of products of damaged or inflamed selftissue, and mounting evidence has linked TLRs activation with the pathogenesis of cancer ( 32), but it is unknown whether NETs require TLRs to exert their functions in DLBCL.…”
Section: Nets Promoted Proliferation and Migration Through The Activamentioning
confidence: 97%